An Assessment of Soil Fertility Management Issues in Koma and Kareta Watershed, Loma Bosa District, Dawro Zone, Southern, Ethiopia - Balcha Gadana, Damte (International Journal For Research In Agricultural And Food Science, 2021)
Changes in traditional ways of cropping and fertility maintenance have posed a serious threat to the sustainability of soil fertility in the mid hills of Ethiopia. This paper tries to bring to the front different issues directly or indirectly related to the sustainability of soil fertility based on a study carried out in Koma Watershed, Dawro zone in 2018. Data was collected through questionnaire survey and focus group discussion and interpretation made using simple statistical tools and logical discussions. Cultivation of short growing season varieties of crops supplemented with high rates of chemical fertilizers has substantially increased the cropping intensity in rainfed Agriculture in Koma. Farm yard manure (FYM) is used in higher proportion than chemical fertilizers both in Koma and Kareta. Nonetheless, Koma land gets lower amount of FYM and higher amount of chemical fertilizers compared to Kareta. Farmers are practicing the traditional method of preparing FYM. Erosion in Kareta and sedimentation in Koma lands are the major threats to soil fertility but no adequate prevention and restoration measures are carried out to cope with these threats. Farmers have not only conserved natural forests but also, planted fodder trees in their farmlands. Nearly half of the demand for forest products is met from the private farmland, which has considerably reduced the pressure on nearby forests. Farmers have markedly positive perceptions regarding the fertilizer application, cropping pattern and importance of forests in farming system.